Dynamics of Competitiveness and Efficiency of Rice Farming in Java Island, Indonesia - Amrina Rosyada; Ramadhani Eka Putra; Wawan Gunawan (3BIO: Journal of Biological Science, Technology and Management, 2022)
Rice is the major crop in Indonesia and the staple food for more than 90% of Indonesians. Given the vital role of rice, efforts to develop rice production are a priority, especially in solving farming efficiency problems. However, inefficiency is one of the major causes of low performance in Indonesian rice production. If farming has high competitiveness and efficiency, Indonesia is encouraged to be able to become an exporter of rice. As a result, national rice farming must continue to improve its competitiveness and efficiency. This study aims to determine the economic efficiency and competitiveness of rice farming in several provinces in Java, i.e., West Java, Central Java, and East Java. The data used in this study is PATANAS survey data obtained from the Center for Socio-Economic Studies and Agricultural Policy, Indonesian Ministry of Agriculture. This study used a quantitative analysis approach and analytical descriptive analysis. The level of competitiveness was analyzed using Policy Analysis Matrix (PAM), while the efficiency level was analyzed using the Stochastic Frontier Method (SFM). The results showed that rice farming in Java Island has a positive profit value on private and social prices. In addition, rice farming in all research locations has competitiveness as measured by indicators of comparative and competitive advantage as characterized by the coefficient values ​​of DRC (Domestic Resource Cost Ratio) and PCR (Private Cost Ratio), which are less than one in the study period 2007-2020. The result of a technical efficiency study shows the average technical efficiency of three provinces in Java is around 0.82, and the factor input that significantly increased the technical efficiency was land and intermediate input.